Arterial stiffening and thickening in patients with pseudoxanthoma elasticum. (March 2018) - Kranenburg, Guido; Visseren, Frank L.J.; de Borst, Gert Jan; de Jong, Pim A.; Spiering, Wilko; ,
Abstract: Background and aims: Patients with pseudoxanthoma elasticum (PXE), a monogenetic calcification disease, are at high vascular risk. Although the precise arterial phenotype remains unestablished, it is hypothesized that PXE predominantly affects the medial arterial layer leading to arterial stiffening. We aimed to test this hypothesis by measuring arterial wall characteristics in PXE and comparisons with the general population and diabetes mellitus type 2 (DM2), a condition typically associated with mixed intimal and medial arterial disease. Methods: Extensive arterial wall characterization was performed in 203 PXE patients involving intima-media thickness (IMT), pulse wave velocity (PWV) and pulse pressure (PP) measurements. IMT and PWV in PXE were compared with the general population using age, sex and mean arterial pressure corrected values for each PXE patient. IMT and PP were compared between PXE and DM2 independently of sex, age and systolic blood pressure, using data of DM2 patients (n = 1033) from the Second Manifestations of ARTerial disease (SMART) cohort. Results: PXE patients had significantly higher IMT (mean difference 0.09 mm; 95% CI 0.07–0.12 mm) and PWV (mean difference 2.5 m/s; 95% CI 1.9–3.0 m/s) compared to the general population. IMT in PXE was lower compared to DM2 (0.72 mm; 95% CI 0.68–0.75 mm vs. 0.85 mm; 95% CI 0.83–0.87 mm, p-value<0.01), whereas PP in PXE was higher compared to DM2 (60 mmHg; 95% CI 59–62 vs. 57 mmHg; 95% CI 57–58 mmHg, p -value<0.01). Conclusions: PXE patients have thicker arterial walls than the general population, but thinner arterial walls than DM2 patients at similar age. Arterial stiffening is more pronounced in PXE patients compared to DM2 patients. Highlights: PXE is associated with a high vascular risk assumed to be caused by medial arterial layer involvement and arterial stiffening. Arterial stiffening and arterial thickening are more extensive in PXE patients compared to the general population. Arterial stiffening is more pronounced compared to DM2 patients of similar age, whereas arterial thickening is not. PXE can be viewed as model disease for medial arterial wall disease with little interference of intimal wall disease.